VALORIZATION OF SINAMI (Oenocarpus mapora H. Karst) OIL CAKE RESIDUAL OBTAINED FROM SCREW PRESS AS A RESOURCE VALUE-ADDED - Ferrer Cutire, Freddy Carlos (2022)
Sinami fruits are an interesting source of promising resources and can be used for the development of functional foods and cosmeceuticals. The objectives of the present study are focused on the evaluation of the proximal composition and chromatic parameters of the cake, the fatty acid profile of the oil obtained by the Folch and Soxhlet methods, and the content of total polyphenols and antioxidant activity of the residue after extraction with n-hexane and chloroform/methanol. The results of this study show that the carbohydrate content was 76,0 g/100 g and crude fiber was 19,20 g/100 g. The chromatic coordinates of the sinami cake presented values of a* = 18,11 and b* = -7,99. The fatty acid profile showed that C18:1n-9/oleic acid, C16:0/palmitic acid, C18:2n-6/linoleic acid are the main fatty acids. Furthermore, the t-test at 5% probability did not show significant differences between the Folch and Soxhlet methods. The extraction yield was higher with n-hexane compared to the chloroform/methanol solvent mixture. Total polyphenol content and antioxidant activity were higher in the residue after extraction with n-hexane. The results of this study provide excellent findings for the use of sinami cake as a partial substitute in commercial products.